Hydrogenation of fluorographite and fluorographene : an easy way to produce highly hydrogenated graphene - Bouša, Daniel (2020)
Fluorographene is an excellent precursor for the synthesis of graphene derivatives. Relative to pure graphene, fluorographene possesses higher reactivity and, in comparison with graphene oxide, is also homogenous in composition, which enables the preparation of well-defined materials. Recently, it has been shown that several graphene derivatives can be synthesized from fluorographene, thus yielding various products such as graphene acid or alkylated graphene. This study focuses on the hydrogenation of fluorographene by using various hydrogenation reactions, including the use complex hydrides and solvated electrons in different media. In addition, a comparison of these reactions shows that fluorinated graphite has significantly lower reactivity than fluorographene. The conversion rates of these reactions are higher when fluorographene is used relative to fluorographite. These reactions can be used to tune the hydrogen/fluorine composition on a graphene backbone.